Efektivitas Influencer Marketing terhadap Loyalitas Konsumen Generasi Z (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of influencer marketing on consumer loyalty of generation Z in Indonesia. Along with the development of technology and the dominance of social media, the marketing approach through influencer figures has become a strategy widely used by companies. Generation Z, which is a consumer group with high exposure to the digital world, tends to be more responsive to authentic and personal content than conventional advertising. This study uses a quantitative method with a survey approach to 150 respondents aged 18–24 years who actively use Instagram and TikTok. The results of the study indicate that influencer credibility, brand suitability, and content engagement levels have a significant influence on consumer loyalty of generation Z. This study provides theoretical and practical contributions to the development of digital marketing strategies based on emotional relationships and social trust.